Transmission of electrical energy : overhead lines /: overhead lines. (2020) - Moura, Ailson P. de (Ailson Pereira); Moura, Adriano Aron F. de (Adriano Aron Freitas); Rocha, Ednardo P. da (Ednardo Pereira)
No abstract available